Memahami Langkah-Langkah dalam Penelitian Etnografi dan Etnometodologi - Khodijah Rezhi; Leli Yunifar; Muhammad Najib (Universitas Galuh, 2023)
The purpose of this paper is to provide an understanding of how the steps in ethnographic research commonly carried out by anthropologists and ethnomethodologies, namely the research tradition of sociologists through literature reviews that produce various views on ethnographic and ethnomethodological research, especially in the steps of implementation both from the birth of the two disciplines to today. The method used in this study uses qualitative methods, with data collection techniques, namely literature studies. The results of this study are steps in ethnomethodological research whose phenomenon is from human actions in a certain community group, which has 3 stages of 10 steps. These ethnographic and ethnomethodological steps are described in detail, each of which has its own characteristics, of course, it can make it easier for ethnographic and ethnomethodological researchers to carry out their research. There needs to be awareness from researchers so as not to rely on abilities without scientific theory, there must be continuity of researchers (students) with experts in their fields (lecturers) so that the research process is accompanied by scientific theory, especially in understanding the steps in ethnographic and ethnomethodological research so that by studying it can produce systematic, effective, efficient and quality research. In modern times, the world of advanced education leads to rational things, to overcome the problem of researchers who ignore understanding the theory of science will make problems if someone who will conduct research, does not understand the steps in research, especially ethnographic and ethnomethodological research.